Let a , b , c , d be the four roots of the equation x 4 − 4 x 3 − 1 6 x 2 − 8 x + 4 = 0 . Find the sum of the absolute values of all possible values of a b + c d .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
How to get intuition about which substitution to make?
Log in to reply
For the equation a x 4 + b x 3 + c x 2 + d x + e = 0 we make the substitution x = y − 4 a b to get a new equation without y 3 term.
This trick is known as depressing a polynomial , another application of it is used in Cardano's method .
is x = y + 1 substitution necessary?
Log in to reply
Maybe not, I used it to make it easier to factor into two quadratic equations, but we can also use other techniques, maybe easier. Also, this is a general method to do that in any quartic equation.
The above equation can be transformed into
( x 2 − 2 x + 2 ) 2 = 2 4 x 2 .
Now from here we get two quadratic equations with roots ( x , y ) , ( p , q ) , respectively.
x 2 − 2 x ( − 6 + 1 ) + 2
And
x 2 − 2 x ( 6 + 1 ) + 2 .
Now sum of all absolute values of a b + c d
= 2 4
Can you please explain your steps with detail? How two quadratics obtained and sum of |ab+cd|? I am completely at loss! Thanks.
Problem Loading...
Note Loading...
Set Loading...
Make x = y + 1 to get a new equation with no cube term: y 4 − 2 2 y 2 − 4 8 y − 2 3 = 0 . Then, factor it into the form ( y 2 + p y + q ) ( y 2 − p y + r ) = 0 . Expanding and comparing coefficients we get the system q + r = p 2 − 2 2 , q − r = 4 8 / p and q r = − 2 3 . Using the identity ( q − r ) 2 = ( q + r ) 2 − 4 q r we get p 6 − 4 4 p 4 + 5 7 6 p 2 − 2 3 0 4 = 0 , which factors as ( p 2 − 2 4 ) ( p 2 − 1 2 ) ( p 2 − 8 ) = 0 .
Now, back to our problem we see that, by Vieta's formula, q = ( a − 1 ) ( b − 1 ) and r = ( c − 1 ) ( d − 1 ) . Adding that we get q + r = a b − a − b + 1 + c d − c − d + 1 or p 2 − 2 2 = a b + c d − ( a + b + c + d ) + 2 or a b + c d = p 2 − 2 0 . Since we have three possible values for p 2 we also have three possible values for a b + c d , which are 4 , − 8 , − 1 2 . Adding their absolute values we get 2 4 .